PENGARUH ARUS KAS DAN PERTUMBUHAN LABA TERHADAP STABILITAS FINANCIAL EMITEN KONSTRUKSI DI BURSA EFEK INDONESIA YANG DI MODERASI PERAN EFISIENSI OPERASIONAL - Nauli, Kembang; Silalahi, Donalson; Munthe, Kornel; Ansella Thalita Hulu, Ruth; Theresia Br Barus, Adriana (CV. Lafadz Jaya, 2025)
This study aims to examine how operational efficiency is perceived to moderate the influence of cash flow and profit growth on the financial stability of companies, particularly in construction companies listed on the Indonesia Stock Exchange (IDX). The approach used is qualitative, based on literature review and conceptual analysis. The results indicate that cash flow is considered a key indicator of business sustainability in the construction sector, while profit growth is understood as a signal of managerial success that requires critical examination. Operational efficiency, which encompasses cost control, project management, and technology utilization, plays a significant role in strengthening the positive impact of cash flow and profit on financial stability. However, contextual factors such as project delays, regulations, and material price fluctuations also influence the effectiveness of this relationship. This study emphasizes the importance of efficiency as an adaptive strategy in building long-term financial resilience in the dynamic and high-risk construction sector.